Everyday Lakota : an English-Sioux dictionary for beginners - 20160731 frey50; Karol, Joseph S.; Rozman, Stephen L.; Dunham, Christine; Rosebud Educational Society; Sinte Gleska College (St. Francis, S.D. : Rosebud Educational Society, 1997)
The "Everyday Lakota conversation tape" consists of English and Lakota with commentary in English. Christine Dunham speaks words and phrases from the Everyday Lakota dictionary for beginners, beginning on p. 88. She speaks first the English word or phrase, and then the Lakota equivalent. The differences between men's and women's questions are described.
The "Everyday Lakota conversation tape" was copyrighted in Mission, S.D. by Sinte Gleske College, c1991.
Keywords: English language -- Dictionaries -- Lakota; Lakota dialect -- Conversation and phrase books; Lakota dialect -- Self-instruction.; Lakota dialect -- Sound recordings for English speakers